The Effect of Physics Instruction on Conceptual Change and Problem-Solving In The Domain of Electric Circuits Among High-Achiever College Students / Beh Kian Lim and Nazlinda Abdullah - Kian Lim, Beh; Abdullah, Nazlinda (Universiti Teknologi MARA Cawangan Pulau Pinang, 2003)
This paper is based on a survey study (Beh and Abdullah, 2002) carried out to explore the effect of Alevel instruction in physics on the formation of useful mental models among 164 high-achiever physics students for problem-solving using simple electric circuits as a context. The results revealed, among other things, that although majority of the students displayed good procedural understanding but among them many had not internalized any of the useful models for electric circuits of the parallel type in terms of current and voltage as presented implicitly in most physics textbooks. However, students who had mastered the practical knowledge of voltage and current achieved a higher rate of success in solving problems. After a year of A-level physics, students show significant improvement in all areas of practical knowledge concerning parallel circuits i.e. practical knowledge of current, voltage and resistance, ability to connect circuits, ability to discern parallel and series connections and ability to solve problems. It is concluded that designing teaching environments that will facilitate students in building internal representations of scientific ideas first before encouraging the repeated practice of procedures should be the emphasis in the science classrooms. A way to facilitate this for parallel circuits is by the explicit use of the two diagrammatical representations for parallel circuits as suggested in the paper.